2022
DOI: 10.3390/bioengineering9080389
|View full text |Cite
|
Sign up to set email alerts
|

Co-Graft of Acellular Dermal Matrix and Split Thickness Skin Graft—A New Reconstructive Surgical Method in the Treatment of Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa is a chronic disease that significantly reduces patients’ quality of life. Patients are chronically treated with systemic therapies, which are often ineffective. Surgical treatment for severe cases of hidradenitis suppurativa is one option for affected patients. Surgical treatment has its limitations, and wound closure may be particularly problematic. This requires the use of reconstructive techniques. The methods of choice for wound closure are split-thickness skin grafts or local fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
(56 reference statements)
0
25
0
Order By: Relevance
“…Some studies analyzed the prevalence and the risk of developing anxiety in HS. In a systematic review and meta-analysis, a prevalence of 12% (95% CI [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]) with an OR of 1.97 (95% CI [1.65–2.35]) was found [ 21 ]. In another meta-analysis and systematic review, Patel et al found that anxiety was present in 18% of patients with HS versus 7% of the non-HS population, while the risk of developing anxiety was twice that of the second population without HS (OR, 2.00; 95% CI, 1.66–2.42) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies analyzed the prevalence and the risk of developing anxiety in HS. In a systematic review and meta-analysis, a prevalence of 12% (95% CI [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]) with an OR of 1.97 (95% CI [1.65–2.35]) was found [ 21 ]. In another meta-analysis and systematic review, Patel et al found that anxiety was present in 18% of patients with HS versus 7% of the non-HS population, while the risk of developing anxiety was twice that of the second population without HS (OR, 2.00; 95% CI, 1.66–2.42) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hidradenitis suppurativa surgery often requires wide excision with problematic wound closure. A new reconstructive technique is represented by the co-graft Acellular Dermal Matrix (an acellular matrix made by collagen) and the Split Thickness Skin Graft [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since Livesey’s potentially useful concept of ADM [ 14 ], ADM has been used in a different new application like hidradenitis suppurativa surgery [ 47 , 48 ], ADM seems to be a biomaterial with great potential. The place of ADM in surgical specialties will extend, and we are sure that we will see a new surgical procedure with ADM.…”
Section: Discussionmentioning
confidence: 99%
“…They implanted ADM in four cases followed by flap reconstruction, in two of the cases ADM was used as a skin substitute (biological dressing), and in 1 case ADM application was followed by skin grafts after 22 weeks of placement of the acellular dermal matrix [ 47 ]. However, the first co-graft of ADM and STSG after wide excisions of Hidradenitis suppurativa during one surgical procedure was performed by Gierek et al (2022) [ 48 ]. ADM co-graft and other applications in hidradenitis suppurativa surgery are presented in Figure 4 .…”
Section: Other Surgical Applicationsmentioning
confidence: 99%
“…Available biomaterials have their advantages and disadvantages [ 18 ]. The co-graft of acellular dermal matrix (ADM) and split-thickness skin graft (STSG) has shown good efficacy as an improved treatment for wide HS excision sites [ 19 ]. This study is a presentation of the treatment results of PRP-assisted reconstructive skin flap surgery methods and the results of ADM and STSG co-graft surgery.…”
Section: Introductionmentioning
confidence: 99%